Cognitive impairment, self‐perceived health and quality of life of older prisoners. (9th March 2017) - Combalbert, Nicolas; Pennequin, Valérie; Ferrand, Claude; Armand, Marine; Anselme, Morgane; Geffray, Brigitte
Abstract: Background: There is a wealth of studies of somatic and mental illness among prisoners, but little on older prisoners and their cognitive aging. Aims: Our study examines the cognitive performance of older male prisoners and its effect on their perceived health and quality of life. Methods: A total of 138 men aged 50 or over were recruited in seven French prisons and 138 men of similar ages from the general population. Two assessments of executive cognitive functions – the mini‐mental state examination and the frontal assessment battery – were administered to each participant, together with self rating schedules of health ( Nottingham Health Profile ), subjective state of mental health and quality of life (the brief World Health Organisation Quality of Life Questionnaire ). Results: There were very significant differences between the two groups in terms of cognitive performance, perceived health and quality of life. There was, however, no significant association between cognitive impairment and perceived health or quality of life. Conclusions: We found evidence that about a fifth of male prisoners in France had executive function test scores suggestive of at least moderately severe dementia and many others some evidence of cognitive impairments. Prisoners suffering from cognitive impairment do not necessarily seek help, perhaps not even considering that their health or quality of life to be affected. Communication deficits may also prevent their participation in prison activities which could prevent, slow or halt cognitive decline. Consequently, it is important that systematic screening for cognitive disorders is offered to men over 50 in prison. Copyright © 2017 John Wiley & Sons, Ltd.